Risk evaluation of outcome of vitreous surgery for proliferative diabetic retinopathy based on vitreous level of vascular endothelial growth factor and angiotensin II. Issue 8 (16th July 2004) - Funatsu, H; Yamashita, H; Noma, H; Mimura, T; Sakata, K; Hori, S
Abstract : Aims: To ascertain whether measurement of the vitreous fluid levels of vascular endothelial growth factor (VEGF) or angiotensin II (Ang II) could predict the outcome of vitreous surgery in patients with proliferative diabetic retinopathy (PDR). Methods: A prospective observational case study was performed in 61 consecutive patients (61 eyes) with PDR who underwent vitreoretinal surgery. Vitreous fluid samples were obtained during surgery. The VEGF level in vitreous fluid and plasma was determined by enzyme linked immunosorbent assay, while the Ang II level was measured by radioimmunoassay. Patients were prospectively followed for 6 months and the postoperative outcome was analysed by logistic regression analysis. Results: No improvement and/or progression of PDR was seen in 15 (25%) of the 61 eyes. Vitreous levels of VEGF and Ang II were significantly higher in eyes with progression of PDR than in eyes with regression of PDR (p = 0.0044, and p = 0.0178, respectively). Multivariate logistic regression analysis showed that the vitreous VEGF level increased along with the progression of PDR after vitreous surgery (odds ratio 2.48, p = 0.0008). Conclusion: A high vitreous fluid VEGF level is associated with a significant risk of postoperative progression of PDR. The vitreous level of VEGF at the time of surgery may be a useful predictor of the outcome.